An application of index number theory to interest rates: Evidence from selected post-Soviet countries - Karen Poghosyan; Ruben Poghosyan (Journal of Central Banking Theory and Practice, 2022)
In this paper, we use index number theory to decompose changes in total interest rate due to changes in the interest rate component and the weight component. We discuss the optimal calculation of a binary index using axiomatic index number theory. Based on this theory we compare alternative indexes and as a result, we choose the Marshall-Edgeworth index because most axioms are satisfied by this index. Comparing the results of binary periods decomposition, we conclude that the differences are not significant when we apply different indices. For multiple period comparison, we suggest using the chain index because it allows accounting for the weights evolution during the whole period. In addition, we derive a formula that could be useful for explaining the differences between chain and direct indexes when we produce multiple period comparison.
Keywords: C43; E43; 330; index number; interest rate; chain and direct indexes; post-Soviet countries